2006
DOI: 10.1002/nau.20361
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle caveolae differentially regulate specific agonist induced bladder contractions

Abstract: Aims: Caveolae are cholesterol-rich plasmalemmal microdomains that serve as sites for sequestration of signaling proteins and thus may facilitate, organize, and integrate responses to extracellular stimuli. While previous studies in the bladder have demonstrated alterations in caveolae with particular physiologic or pathologic conditions, little attention has been focused on the functional signi¢cance of these organelles. Therefore, the purpose of this study was to investigate the role of caveolae in the modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…As the functional attributes of caveolae are probably determined by the complex relationship among the different combinations of caveolin proteins represented in caveolae, we comprehensively examined the caveolin isoform distribution and interaction to begin to unravel the role The present data show an isoform-specifi c and region-dependent distribution of caveolin gene and protein expression in BSM. Consistent with previous observations [ 14,18 ] , widespread Cav-1 expression was detected throughout the bladder wall. Interestingly, regional differences in Cav-2 immunoreactivity did not parallel that of Cav-1, but showed graded attenuation of intensity in BSM across layers from submucosa to serosa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As the functional attributes of caveolae are probably determined by the complex relationship among the different combinations of caveolin proteins represented in caveolae, we comprehensively examined the caveolin isoform distribution and interaction to begin to unravel the role The present data show an isoform-specifi c and region-dependent distribution of caveolin gene and protein expression in BSM. Consistent with previous observations [ 14,18 ] , widespread Cav-1 expression was detected throughout the bladder wall. Interestingly, regional differences in Cav-2 immunoreactivity did not parallel that of Cav-1, but showed graded attenuation of intensity in BSM across layers from submucosa to serosa.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the role of these proteins in cell signalling has generally been studied only in cell types in which either Cav-1 or Cav-3 predominate. We and others have previously shown that urinary BSM, unlike non-SM cells and certain other SM systems, expresses all three caveolin isoforms [ 13,14,17 ] . As the functional attributes of caveolae are probably determined by the complex relationship among the different combinations of caveolin proteins represented in caveolae, we comprehensively examined the caveolin isoform distribution and interaction to begin to unravel the role The present data show an isoform-specifi c and region-dependent distribution of caveolin gene and protein expression in BSM.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The cholesterolenriched domains of the cell membrane (6) play several important roles in cellular processes (7,8). They also provide a platform for G-protein, tyrosine kinase, and GTPase-mediated signaling in the detrusor membrane (9,10). Alterations in plasma cholesterol levels are closely related to membrane cholesterol, which in turn modulates signaling through the detrusor smooth muscle membrane (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…They also provide a platform for G-protein, tyrosine kinase, and GTPase-mediated signaling in the detrusor membrane (9,10). Alterations in plasma cholesterol levels are closely related to membrane cholesterol, which in turn modulates signaling through the detrusor smooth muscle membrane (8)(9)(10)(11). Based on this knowledge, it is natural to expect alterations of urinary bladder functions in response to changing plasma cholesterol.…”
Section: Introductionmentioning
confidence: 99%